MANAJEMEN PENGETAHUAN DI HERBARIUM: STUDI KUALITATIF MANAJEMEN PENGETAHUAN DALAM ASPEK PRESERVASI PENGETAHUAN KURATOR DI HERBARIUM BANDUNGENSE - Ardhian, Reza; Erwina, Wina; Perdana, Fitri (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
(Objectives) This study aims to examine the implementation of knowledge management in the aspect of knowledge preservation by herbarium curators, specifically through three main processes: selection, storage, and actualization. (Method) The method used is qualitative research with a case study approach, which includes in-depth interviews with the head and curator of Herbarium Bandungense as primary data sources, as well as field observations. Secondary data were obtained through online literature and social media, while data analysis was carried out thematically, and the results were presented in the form of descriptive narratives. (Finding) The results showed that at the selection stage, the knowledge that was prioritized included knowledge that was not written in reference books and information that could improve curatorial effectiveness, which was strengthened by external collaboration. At the storage stage, knowledge was stored in three forms: individual, through social incentives and organizational climate flexibility; collective, through formal documentation such as Standard Operating Procedures (SOPs) or manuals; and electronic, with the use of online chat groups. At the actualization stage, knowledge was applied in daily operations through SOP guidelines and routine decision-making. This study also identified several challenges, such as limited collaboration and human resources, lack of faculty attention to herbarium management, and minimal involvement of curators in strategic decision-making, especially related to herbarium sustainability and effectiveness policies. As a recommendation, this study suggests increasing attention to herbarium needs, especially in terms of funding and manpower. In addition, the establishment of a national association for herbarium curators is considered important to encourage the exchange of information on a wider scale. Finally, this study emphasizes the importance of increasing curator involvement in formulating strategic policies so that the sustainability of herbarium management can be guaranteed.